Relationship between Access to Health Services and Quality of Health Services with Compliance with Tuberculosis Treatment in Kolaka Regency - Ida Purwastuti; Rahmawati Rahmawati; Sunarsih Sunarsih (Waluya The International Science of Health Journal, 2026)
Introduction: This study examines the factors associated with low tuberculosis treatment coverage in Kolaka Regency using a cross-sectional study design. The main objective of this study is to examine the relationship between access to health services and quality of health services with compliance with tuberculosis treatment in Kolaka Regency. Method: This type of research is quantitative, design cross-sectional study. The study was conducted at 14 Community Health Centers in Kolaka Regency. The study population consisted of 449 confirmed tuberculosis patients, with a sample of 208 patients taken using the cluster simple random sampling method. The sample distribution was carried out according to the population proportion in each community health center. Result: The calculated X²count of 37.627 indicates a significant difference, with a correlation coefficient (ϕ) of 0.436 indicating a moderate relationship between access to health services and the calculated X²count of 9.504 indicating a significant relationship, with a correlation coefficient (ϕ) of 0.224 indicating a weak relationship between the quality of health services and medication adherence. Conclusion: Develop an effective monitoring system to monitor the quality of healthcare services and medication adherence and integrate service quality data into healthcare applications.